2020
DOI: 10.1186/s13071-020-04282-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of Anopheles coustani and Anopheles arabiensis to the transmission of Plasmodium falciparum and Plasmodium vivax in two neighbouring villages of Madagascar

Abstract: Background: Malaria is still a heavy public health concern in Madagascar. Few studies combining parasitology and entomology have been conducted despite the need for accurate information to design effective vector control measures. In a Malagasy region of moderate to intense transmission of both Plasmodium falciparum and P. vivax, parasitology and entomology have been combined to survey malaria transmission in two nearby villages. Methods: Community-based surveys were conducted in the villages of Ambohitromby a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
12
1
Order By: Relevance
“…coluzzii . This result contradicts findings from Goupeyou-Youmsi et al [ 38 ] obtained in two neighboring villages of the rural commune of Andriba in Madagascar. Indeed, they found that An.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…coluzzii . This result contradicts findings from Goupeyou-Youmsi et al [ 38 ] obtained in two neighboring villages of the rural commune of Andriba in Madagascar. Indeed, they found that An.…”
Section: Discussioncontrasting
confidence: 99%
“…arabiensis was the vector of three Plasmodium species ( P. falciparum , P. vivax , and P. malariae ). These differences could be explained by weather conditions, the ecological environment, and/or the geographical distribution of vectors that are different between countries [ 38 ]. These results suggest that more screening of An.…”
Section: Discussionmentioning
confidence: 99%
“…In Nouakchott, until proven otherwise, malaria parasites are transmitted exclusively by An. arabiensis, which can transmit both P. vivax and P. falciparum, as demonstrated in other African countries where P. vivax and P. falciparum are sympatric [43][44][45]. It is therefore not easy to understand why P. falciparum has been responsible for only a minority of malaria infections in Nouakchott until present.…”
Section: Discussionmentioning
confidence: 99%
“…Immunological studies using wild catch mosquitoes of An. coustani in different countries in sub-Sharan Africa have shown its susceptibility to P. falciparum and P. vivax infection [33][34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%